Theory and analysis of the loop antenna and Ω-shaped loop-dipole antenna - Fang, Yulin (2023)
This paper first examines and corrects Storer's theory of circular loop antennas, and then investigates theoretically the proposed Ω-shaped loop-dipole antenna. Special emphasis is given to the analysis of the effect of the higher-order terms of the Fourier series as a remainder on the current distribution, input impedance, and radiation patterns of the thin-wire circular loop antenna. It is found that the remainder must be included in the calculation of the current distribution and input impedance but can be neglected to simplify the calculation of far-field radiation. Then, a theoretical model is proposed to analyze the radiation fields, directivity, and input impedance of the proposed Ω-shaped loop-dipole antenna based on the loop and dipole antennas' theories. Analytical expressions for the radiation fields, directivity, and input impedance of the Ω-shaped loop-dipole antenna are derived. The theoretical and numerical results are compared for the Ω-shaped loop-dipole antennas of practical interests. They are in good agreement.